(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
In this article we deal with aspects of the recognition of the socio-affective Membership and its importance in the context of contemporary Families; so we get to know the family unit, its origin and formation, their needs, claims and demands in the legal odenament in order to enter this family, membership, and the bond of emotional and affective considering, conceptualizing and comparing the legal significance affection, given the biological bond, widely debated and, at least in its most common feature, already pacified by the doctrine and jurisprudence. Society and model families become with the passage of time. Today, in search of a greater good family relationships, the judges increasingly realize the need viable solutions to remedy the merits of Negatorias Shares Shares Parenthood and Civil Registration denial. Thus, often the absence of a biological fact, is less relevant element for the protection of child and adolescent. Whereas one can not speak in socioafetiva membership without the affection is present, this is the aim of this study, collaborate and help conceptualize and define affection, family and elements of socio-affective maternity and paternity, the current concept of multiparentalidade in face Brazilian law and jurisprudence, doctrine and their Stocks Membership Recognition socio-affective or socio-affective action declaratory membership. the absence of a biological fact, is less relevant element for the protection of child and adolescent. Whereas one can not speak in socioafetiva membership without the affection is present, this is the aim of this study, collaborate and help conceptualize and define affection, family and elements of socio-affective maternity and paternity, the current concept of multiparentalidade in face Brazilian law and jurisprudence, doctrine and their Stocks Membership Recognition socio-affective or socio-affective action declaratory membership. the absence of a biological fact, is less relevant element for the protection of child and adolescent. Keywords: Affection, Social Affiliation, Children, Constitutional Recognition, Family.